Dissipation kinetics and pre‐harvest residue limit of pyriofenone in oriental melon (Cucumis melo Var. makuwa) grown under regulated climatic conditions. (21st March 2017) - Chung, Hyung Suk; Kabir, Md. Humayun; Abd El‐Aty, A.M.; Lee, Han Sol; Rahman, Md. Musfiqur; Chang, Byung‐Joon; Shin, Ho‐Chul; Shim, Jae‐Han
Abstract: A high‐performance liquid chromatography–ultraviolet detection was used to estimate the disappearance rates as well as the pre‐harvest residue limits of pyriofenone in oriental melon ( Cucumis melo var. makuwa ) grown under greenhouse conditions in two different locations (A and B) in Seongju, Republic of Korea. The identity of the compound in standard solution and representative field incurred samples was confirmed using liquid chromatography–tandem mass spectrometry. The method was validated in terms of linearity, limits of detection and quantification, accuracy (expressed as recovery) and precision (expressed as relative standard deviation) for accurate and precise quantitation. Notably, the residual levels of field incurred samples collected over days 0–10 post‐application were below the maximum residue level (0.2 mg/kg) established by the Korean Ministry of Food and Drug Safety. Site A showed lower residue levels and a higher decline rate than site B, which might be attributed to seasonal variation (high temperature) and increased metabolic and enzyme profiling in the mature fruits. The half‐lives were similar, 4.9 and 4.3 days, at sites A and B, respectively. Using the pre‐harvest residue limit, we predicted the residue amounts at 10 and 5 days before harvest, which resulted in concentrations lower than the provisional maximum residue level at harvest time.